Effects of UV-B Radiation on Near-Infrared Spectroscopy and Identification of Puccinia striiformis f. sp. tritici - Cheng, Pei; Li, Xiaolong; Qin, Feng; Zhao, Longlian; Li, Junhui; Ma, Zhanhong; Wang, Haiguang (Journal of Spectroscopy, 2014)
Based on near-infrared spectra of three physiological races of Puccinia striiformis f. sp. tritici (i.e., CYR31, CYR32, and CYR33) irradiated under four UV-B intensities (i.e., 0, 150, 200, and 250 μw/cm2), the effects of UV-B radiation on near-infrared spectroscopy of the pathogen were investigated in spectral region 4000–10000 cm−1, and support vector machine models were built to identify UV-B radiation intensities and physiological races, respectively. The results showed that the spectral curves under UV-B radiation treatments exhibited great differences compared with the corresponding control treatment (0 μw/cm2) in the spectral regions 5300–5600 cm−1 and 7000–7400 cm−1 and that the absorbance values of all the three physiological races increased with the enhancement of UV-B radiation intensity. Based on near-infrared spectroscopy, different UV-B radiation intensities could be identified and different physiological races could be distinguished from each other with high accuracies. The results demonstrated the utility and stability of the proposed method to identify the physiological races.